2002
DOI: 10.1210/mend.16.6.0852
|View full text |Cite
|
Sign up to set email alerts
|

Cis- and Trans-Activation of Hormone Receptors: the LH Receptor

Abstract: G protein-coupled receptors (GPCRs) accommodate a wide spectrum of activators from ions to glycoprotein hormones. The mechanism of activation for this large and clinically important family of receptors is poorly understood. Although initially thought to function as monomers, there is a growing body of evidence that GPCR dimers form, and in some cases that these dimers are essential for signal transduction. Here we describe a novel mechanism of intermolecular GPCR activation, which we refer to as trans-activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 106 publications
2
27
1
Order By: Relevance
“…It is interesting to note that the coexpression of two different CXCR2 mutations, one lacking the N-terminal (involved in chemokine binding) domain, Y49-CXCR2, and one lacking the whole C-terminal domain (involved in signaling), CXCR2-A315, did not restore cell signaling and chemotaxis, indicating that receptor activation upon agonist binding implicates an intramolecular mechanism. This is different from what has been reported for other GPCRs, like the luteinizing hormone receptors (44), and indicates a mechanism of cis-activation for CXCR2 composing the dimers.…”
Section: Discussioncontrasting
confidence: 99%
“…It is interesting to note that the coexpression of two different CXCR2 mutations, one lacking the N-terminal (involved in chemokine binding) domain, Y49-CXCR2, and one lacking the whole C-terminal domain (involved in signaling), CXCR2-A315, did not restore cell signaling and chemotaxis, indicating that receptor activation upon agonist binding implicates an intramolecular mechanism. This is different from what has been reported for other GPCRs, like the luteinizing hormone receptors (44), and indicates a mechanism of cis-activation for CXCR2 composing the dimers.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, nonfunctional hormone-receptor complexes formed by binding of hCG to nonsignaling LH receptor mutants exhibit faster rotational diffusion (54) than do functional hormone-occupied LH receptors (55), no increase in FRET in response to ligand (4) and are not confined in either raft domains or membrane microdomains examined using single particle tracking (7). These results suggest that the slower lateral dynamics observed for Au-DG-hCG when cells are treated with hCG may result from a bystander effect on Au-DG-tagged receptors that may include direct interactions between hCG-occupied LH receptors and the Au-DG-hCG occupied receptors similar to LH receptor trans-activation described by Ji and co-workers (56).…”
Section: Discussionsupporting
confidence: 61%
“…Evidence pointing toward this goes back to as early as the 1980s when data from equilibrium sedimentation of detergent-solubilized LHR and radiation inactivation of LHRs on gonadal cells suggested that the LHR may be present in a dimeric or oligomeric form (31,32). More recently, functional complementation studies further suggested the dimerization of the LHR (33,34). Direct evidence in support of dimerization of the LHR has been obtained using fluorescent resonance energy transfer (FRET) (35)(36)(37)(38) as well as our studies demonstrating specific co-immunoprecipitation of differentially tagged forms of the LHR (39).…”
mentioning
confidence: 64%